Perlindungan Hukum Terhadap Anak Korban Kejahatan Seksual dalam Perspektif Hukum Progresif - Harahap, Irwan Safaruddin (Jurnal Media Hukum, 2016)
A child has the right in the same as like own adult people. There are not many people that have thought to do certain things with Children’s right protection. So there are some efforts to protect children’s right that have been broken by country, adult, their environment, or their parents that did not give much attention to their future. Whereas, child as the soul and the reflection of the future, family asset, religion, and nation. Child get bad experience, like children exploitation, children abusement, being sex toy, child labor, abandoned, become the street children, victims of drug trafficking. Universally, Indonesia in breaking of the children’s right in real or nonreal become a normal and common image as mass media gives news about that. Indonesia as a law nation based on Pancasila must give a law protection to society, because of that the law protection will produce confession and human rights protection in his shape as individual creatures and social creatures in a unitary state that uphold family spirit in order to attain public welfare. Law enforcement to child victims of sexual crime in North Sumatra as conceptually has been located on the harmonizing relations of the values which span the hierarchy activities in good rules and with attitude as series value hierarchy, to build, maintain, and defend the peacefulness social life, conception that has basic philosophy that makes more solid. Construction law to protection children victims of sexual crime in progressive law perspective is an ideology and dedication of the perpetrators of law got the first place to do a dignification.